Water for Everyone - Ashagre, Biniam; White, Sue; Mwakalila, Shadrack; Platts, Philip; Schaafsma, Marije; Smith, Celina J. (Tanzania Forest Conservation Group, 2014)
Around one in ten Tanzanians source their water from rivers originating in the Eastern Arc Mountains (EAM). In Dar es Salaam, the main water source is the Ruvu River, flowing from Uluguru Nature Reserve, from which around 300 million litres are extracted daily. Moreover, at least half of Tanzanian hydroelectricity is generated from EAM rivers. The EAM contain moist forest assemblages as well as large areas of miombo woodland at lower elevations and on drier leeward aspects. These biomes are believed to play significant roles in the regulation of hydrological flow, flood mitigation and soil conservation. Despite this hypothesised importance, the interactions between river flow, habitat type and land use are not well understood. To explore these complexities, the Valuing the Arc programme (VTA) parameterised a detailed, daily water model called SWAT to model the hydrology of two focal catchments: the Sigi in Tanga Region and the Ruvu in Morogoro region. In addition, we developed a broader scale, monthly model (WatR) to tentatively explore hydrological flow across the wider VTA region.